2019
DOI: 10.1111/myc.12966
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary cryptococcosis characteristics in immunocompetent patients—A 20‐year clinical retrospective analysis in China

Abstract: SummaryBackgroundPulmonary cryptococcosis (PC) is not considered an rare, opportunistic infection anymore. The immunocompetent population accounts for an increasing proportion of the morbidity.ObjectiveThis study investigated the clinical characteristics of PC patients spanning 20 years, in a referral centre of China.Patients/MethodsWe retrospectively investigated the clinical data of 99 patients with PC who were diagnosed at Peking Union Medical College Hospital (PUMCH) from January 1998 to December 2017.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
4
25
0
1
Order By: Relevance
“…3,12 When immunocompromised hosts are infected with Cryptococcus, the CNS is easily infected once symptoms occur in the lungs. 13 The most common symptoms of PC found in our study sample were cough (51.6%) and expectoration (38.2%), which is similar to previous reports. [13][14][15] Common clinical symptoms of CNS involvement are headache, fever, and chills, and the risk of CNS involvement is significantly increased when symptoms of fever and headache are present.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3,12 When immunocompromised hosts are infected with Cryptococcus, the CNS is easily infected once symptoms occur in the lungs. 13 The most common symptoms of PC found in our study sample were cough (51.6%) and expectoration (38.2%), which is similar to previous reports. [13][14][15] Common clinical symptoms of CNS involvement are headache, fever, and chills, and the risk of CNS involvement is significantly increased when symptoms of fever and headache are present.…”
Section: Discussionsupporting
confidence: 91%
“… 3 , 12 When immunocompromised hosts are infected with Cryptococcus , the CNS is easily infected once symptoms occur in the lungs. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many previous studies have reported that cryptococcosis was more common in immunocompetent patients in China [17][18][19] . Another recent report showed 40.4% PC patients had normal immune function 12 . Although some patients with cryptococcosis seemed to be immunocompetent, some immune gene characteristics such as mannose-binding www.nature.com/scientificreports www.nature.com/scientificreports/ how to correctly evaluate immune function of patients is a problem that needs to be solved.…”
Section: Discussionmentioning
confidence: 88%
“…This is the reason why disseminated cryptococcosis is more common in patients with an impaired immune function such as HIV. In HIV-uninfected patients, other underlying condition that have been identified include liver cirrhosis, diabetes mellitus, and autoimmune diseases [ 5 , 6 ]. However, no immunosuppressive condition, diabetes mellitus, chronic kidney disease, steroid use, or close contact with pigeon or bird droppings was identified in our patient.…”
Section: Discussionmentioning
confidence: 99%